Lack of Correlation between Anticoagulant Activity and Phospholipid Hydrolysis by Snake Venom Phospholipases A2 - Condrea, Eleonora; Yang, Chen-Chung; Rosenberg, Philip (Thrombosis and Haemostasis, 1981)
The anticoagulant effects and the simultaneous plasma phospholipid hydrolysis induced by three purified phospholipases obtained from snake venoms, i.e., the basic, relatively toxic N. nigricollis, the neutral, relatively nontoxic H. haemachatus, and the acidic, relatively nontoxic N. n. atra, have been compared. The N. nigricollis phospholipase has a very strong anticoagulant effect at concentrations which induce relatively low levels of phospholipid hydrolysis in plasma. The H. haemachatus and N. n. atra phospholipases become anticoagulant only at high concentrations, and the associated phospholipid hydrolysis is also very high. It is concluded that, while all phospholipases are likely to inhibit coagulation if used in amounts sufficiently large to deplete plasma of phospholipids, strongly active phospholipases, such as N. nigricollis, interfere nonenzymatically with the clotting process before any appreciable phospholipid hydrolysis is reached.
Keywords: Snake venom; Phospholipase A2; Anticoagulant effect; Phospholipid hydrolysis